Pertimbangan realistis dan non-realistis dalam soal cerita matematika dengan siswa kelas delapan Meksiko - Martínez-Meléndez, Karol Mayreni; Juárez-López, José Antonio; Díaz-Espinoza, Irving Aarón (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
The present exploratory study with a qualitative approach had the objective of analyzing the type of realistic and unrealistic responses, as well as the considerations of the real-world environment in second grade high school students in Mexico in the resolution of mathematical verbal problems. To this end, students were presented with several realistic and pseudorealistic verbal problems of proportionality, false proportionality, division with remainder and arithmetic operations. Two data collection instruments were created: a verbal problem sheet and a questionnaire. The responses were classified as realistic, unrealistic, and other responses. This research showed that some of the students conceived realism in the answers based on the interpretation they were able to make of the context of the problem. That is, they took realism into account in their solution, through comments or arguments from their own experiences, by analyzing their mathematical answers to link them with the existing knowledge they have of the real world. The study contributes to the understanding of how students’ cultural background and everyday life experiences influence their approach to mathematical problem-solving, highlighting the importance of context in shaping students’ problem-solving strategies. This finding emphasizes the need for educators to recognize the value of incorporating realistic contexts in mathematical instruction to enhance students’ engagement and understanding.